2018
DOI: 10.1111/jsr.12801
|View full text |Cite
|
Sign up to set email alerts
|

Mood impairment is stronger in young than in older adults after sleep deprivation

Abstract: Sleep deprivation commonly impairs affective regulation and causes worse mood. However, the majority of previous research concerns young adults. Because susceptibility to sleep deprivation and emotion regulation change distinctively across adult age, we tested here the hypothesis that the effect of sleep deprivation on mood is stronger in young than in older adults. In an experimental design, young (18–30 years) and older adults (60–72 years) participated in either a sleep control (young, n = 63; older, n = 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 51 publications
2
38
1
4
Order By: Relevance
“…In the EROS study, although sleep duration did not have a role in psychological function, unlike previous studies, that strongly correlated sleep duration with mood states (49,55,56). Sleep quality was strongly correlated with better psychological outcomes, including lower depression and fatigue, and higher vigor, indicating that sleep quality led to a global improvement in mood, similarly to what has been unanimously observed (49,55,(57)(58)(59). We speculate that sleep duration was not demonstrated to a major factor of mood states or any other characteristic in athletes because in higher quality sleep duration tends to play a less important role (60,61).…”
Section: Linear Correlationsmentioning
confidence: 48%
“…In the EROS study, although sleep duration did not have a role in psychological function, unlike previous studies, that strongly correlated sleep duration with mood states (49,55,56). Sleep quality was strongly correlated with better psychological outcomes, including lower depression and fatigue, and higher vigor, indicating that sleep quality led to a global improvement in mood, similarly to what has been unanimously observed (49,55,(57)(58)(59). We speculate that sleep duration was not demonstrated to a major factor of mood states or any other characteristic in athletes because in higher quality sleep duration tends to play a less important role (60,61).…”
Section: Linear Correlationsmentioning
confidence: 48%
“…The majority of reviews support the conclusion by Nielsen, et al that a short sleep duration consistently is associated with development of obesity in children and young adults, but not consistently so in older adults (7). It has also been shown that sleep deprivation has a stronger effect on mood impairment in young adults compared to in older adults (10) making it an important factor for the well-being of a young adult person.…”
Section: Introductionmentioning
confidence: 76%
“…Estudos apontam para diversos prejuízos à saúde decorrentes do trabalho em turnos, tais como o aumento de peso corporal (MCHILL et al, 2014) e obesidade (TAHERI et al, 2004 (TSAI et.al., 2017) (COVASSIN et al, 2016) (MACAGNAN et al, 2012, a deterioração do padrão de sono (KECKLUND; AXELSSON, 2016) (HULSEGEE et al, 2018) (BASNER; DINGES, 2011) (SHORT et al, 2015) e o desalinhamento circadiano . Evidências recentes demonstram ainda que o trabalho em turnos está associados a prejuízos no desempenho psicomotor, tais como a queda na atenção (BASNER et al, 2017), perda de memória (RAVEN et al, 2018), vagarosidade na "tomada de decisão" (BROWN et al, 2012), prejuízos no humor (SCHWARZ et al, 2018), problemas psíquicos, motores, sociais e familiares, além de absenteísmo e maior risco de acidentes (RAJARATNAM, 2011) (FERGUSON et al, 2012). Até o momento não há um consenso sobre qual programa de turnos teria um menor impacto na saúde e no desempenho psicomotor, e questões referentes à melhor velocidade para rotação dos turnos (rotações rápidas ou lentas), o melhor sentido da rotação (horário ou anti-horário) (SALLINEN; KECKLUND, 2018), tipo de turno e sequência mais nociva ao desempenho (VEDAAAB et al, 2015) continuam sem respostas.…”
Section: Introductionunclassified
“…Recent evidence demonstrates that shift work is related to negative effects on psychomotor performance (Fisk et al, 2018) which is defined as the ability to maintain and process information for decision making in the workplace (Marek et al,2010). These negative effects include cognitive impairments such as attention drop (Basner et al, 2017), memory (Raven et al, 2017), decision making (Brown et al, 2012), mood alteration (Schwarz et al, 2018), psychic, motor, social and family problems, as well as absenteeism and increased risk of accidents (Rajaratnam et al, 2011) (Ferguson et al, 2012). One of the main triggers for such impairments appears to be deterioration of the sleep pattern (Hulsegee et al, 2015) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation